Performance Degradation of PV Module Due to Different Types of Dust Pollutants - Kumar Tripathi, Abhishek; Aruna, M.; S.N. Murthy, Ch.; ., . (International Journal of Engineering and Technology, 2018)
The deposition of dust on photovoltaic (PV) module surface is the main cause for its performance degradation in an open atmosphere. The performance degradation of the module due to dust deposition depends on the size, density and type of dust. In this paper, the effect of two different types of dust pollutants, such as red soil and lime stone on PV module performance was studied. It was found that the reduction in PV module performance due to red soil dust was more emphatic than the lime stone dust. Moreover, the dust deposition on the module surface shows a significant reduction in short circuit current and power output of PV module when compared to its open circuit voltage.Â Â